PHILOSOPHICAL AND ANTHROPOLOGICAL IMPORTANCE OF DEVELOPMENT OF ARTIFICIALLY CREATED INTELLIGENT SYSTEMS - Yu. D. Gensitskiy (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. Understanding the philosophical and anthropological importance of the development the artificial intelligence systems requires the analysis of the socio and anthropological content of intercomputer problems of interaction in the context of media philosophical praxis, anthropological maintenance of intellect nature, considering the specifics of the concept of artificial intelligence systems in the environment of M2M development of socio-cognitive practices of intercomputer interaction of social and humanitarian potential. Methodology. The implementation target is seen in the use of scientific and theoretical basis of the media philosophical, philosophical anthropology, the media philosophical approach to understanding society, science and technology, the use of publications on selected topics of research. Scientific novelty. The concept of artificial intelligence systems in the aspect of social and humanitarian potential of their formation and development in the environment of M2M was considered. The problems of machine learning as technology transformation M2M were analysed. The anthropological threats to the development of artificially created intelligent systems were defined. Conclusions. From the global risks point of view, one of the most critical circumstances due to the artificial intelligent system can strengthen its intelligence very quickly. The obvious reason for suspecting such an opportunity – a recursive self-improvement. Such system becomes smarter, including the intelligent writing of internal cognitive function, that the ability to rewrite their existing cognitive function to make it work better. This will make such systems more intelligent, and smarter in terms of the processing itself. The success of artificial intelligence may be the beginning of the end of the human race. Almost any technology falling into malicious hands reveals the potential for harm, but when it comes to artificial intelligent system, there is a new problem with the fact that these malicious hands may belong to the technology itself.